CHEMICAL REAGENTS FOR SELECTIVITY IN IMPROVEMENT OF RHEOLOGICAL PROPERTIES OF CRUDE OIL - VALI HANAQA NURULLAYEV; BEYBALA TACI USUBALIYEV; FIKRET SULEYMAN GEHREMANOV; ULKER FIKRET GEHREMANOVA (Journal of Engineering Studies and Research)
Today oil industry – one of the most developing and priority industries of Azerbaijan which plays a huge role in national economy. The need for this mineral constantly increases therefore for improvement of quality and decrease in cost of the product mining companies need to modernize constantly not only the oil-field equipment, but also to improve production processes. Now the increasing number of high-sulphurous and high-paraffinic oil fields is brought into development. As a result, the corrosion rate of the oil-field equipment increases, the output of wells decreases and expenses of mining companies in general raise.